Alternative ways of evaluation of commercial bank’s financial soundness on an example of JSC «Prominvestbank» - Burlutska, Svitlana; Astakhov, Anton (My University, 2012)
Thereby both Kromonov’s and Lerner’s methods prognosticate a new liquidity crisis for JSC «Prominvestbank». In general, these methods appeared to be representative and relatively thorough. They are mainly designed for quick estimation of financial soundness for internal purposes and cannot replace completely specialized agencies’ services and IMF’s recommendations. However, in some cases they might play a role of an extremely helpful instrument and become an additional means of financial hedge against unexpected circumstances.
Keywords: криза ліквідності; фінансова стійкість; комерційний банк; liquidity crisis; financial stability; commercial bank; кафедра економіки праці та менеджменту